The Conceptual Matrix of the Individual age Maturity in the Context of Readiness for Retirement - Magdysyuk, Liudmyla (Psychological Prospects Journal, 2014)
The article contains results of theoretical analysis of age maturity of the individual in the context of its readiness for retirement. The dynamics of age periodization of scientific thought is reported. It is mentioned that the maturity is the longest period of personal development, which is characterized by a tendency to achieve the highest spiritual, intellectual and physical abilities. The use of chronological age is conditional, because within a socio- historical period, one culture, one age cohort there are a variety of great individual differences. It is claimed that there are four kinds of ages: chronological, biological, social and psychological. Outlined are the main tasks of the maturity periods. The main age new formation of the maturity period may be considered productivity. It is noted that the problem of the Ukrainian society is the perception of senior citizens through the prism of stereotypes that define a negative attitudes of young people, which manifests itself as a social phenomenon of «ageism». It is suggested a conceptual model of psychological readiness of people to retire, on the basis of personal activity approach. The components of psychological readiness (cognitive, emotional and volitional, motivational, conative) are substantiated to ensure the efficiency and effectiveness of painless termination of professional activities. It is established the psychological readiness of the individual components of late maturity before entering the retiremen which are: cognitive – the need of man to receive the necessary knowledge, ability to mobilize their knowledge and experience; emotional and volitional functions as improving the skills of psychic self-regulation, self-control; motivational function is the orientation of the individual to the positive perception of environment, its future, the perception of self-worth; conative function guides the individual to a particular behavior (sports, hobbies and recreational activities).